Oxalic acid eutectic of PARP7 inhibitor and preparation method of oxalic acid eutectic

The formation of a co-crystal with grass acid stabilizes the PARP7 inhibitor, addressing the issues of instability and reproducibility, resulting in improved pharmacokinetic properties and bioavailability.

CN119684268AActive Publication Date: 2025-03-25NOVOSTAR PHARM LTD

Patent Information

Application Number
CN202411878352.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-25
Estimated Expiration
2044-12-19

AI Technical Summary

Technical Problem

The existing PARP7 inhibitors have poor pharmacokinetic properties and are limited in clinical development due to their instability and lack of a stable crystal form, leading to multiple crystal types and poor reproducibility in production.

Method used

A stable crystal form of the PARP7 inhibitor is achieved through the formation of a co-crystal with grass acid, which stabilizes the structure via hydrogen bonding, improving solubility and reducing moisture absorption, and is produced using a method involving mixing the inhibitor with grass acid in a solvent and subsequent drying.

Benefits of technology

The co-crystal form of the PARP7 inhibitor exhibits improved stability, solubility, and reduced moisture absorption, enhancing its bioavailability and simplifying production, making it suitable for clinical development.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119684268A_ABST
    Figure CN119684268A_ABST
Patent Text Reader

Abstract

Eutectic comprising compound of Formula 1 and oxalic acid, # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the pharmaceutical field, and in particular to an oxalic acid cocrystal of a PARP7 inhibitor and a preparation method thereof. Background Art

[0002] PARP (poly ADP-ribose polymerase) is a protein family composed of 17 enzymes. It uses nicotinamide adenine dinucleotide (NAD+) as a substrate to transfer ADP-ribose (ADPR) to target proteins. It is a multifunctional protein post-translational modification enzyme present in most eukaryotic cells. It is activated by recognizing structurally damaged DNA fragments and is considered a sensor of DNA damage, participating in a series of cellular processes such as DNA repair and genome stability.

[0003] The PARP family is divided into two subclasses: polyPARPs and monoPARPs. PolyPARPs add multiple ADPR (ADP-ribose) molecules to the protein sequentially, resulting in ADPR chains that can reach hundreds of units. In contrast, monoPARPs modify proteins by attaching only one ADPR molecule. Therefore, polyPARPs and monoPARPs represent two different types of therapeutic targets because they have different ADP-ribosylated protein substrates and play different roles in cell signaling and protein function regulation.

[0004] PARP7 (TIPARP) is a monoPARP and a key factor in regulating innate immunity, transcription factor activity and cellular stress response. Several studies have shown that PARP7 plays a key role in the innate immune signaling pathway, especially as a negative regulator of type I interferon antiviral response. Knockout of PARP7 can enhance the expression of interferon-β (IFN-β) induced by nucleic acid sensor agonists or viruses in different cell types. PARP7, as an inhibitor of aryl hydrocarbon receptor (AHR) activity, is upregulated in cellular stress activated by AHR after viral infection or exposure to cigarette smoke. In addition, PARP7 is also regulated by liver X receptors (LXRs) and hypoxia-inducible factor 1 (HIF-1).

[0005] There are relatively few PARP7 inhibitors reported so far, and the most advanced ones are still in the early clinical development stage, and often have problems such as poor pharmacokinetic properties in vivo. CN115785074B provides a RARP7 inhibitor that can improve pharmacokinetic properties in vivo, has better anti-tumor activity and therapeutic effects, reduces clinical side effects, and can be expanded to more tumor indications.

[0006] Among them, Example 25 of CN115785074B discloses the synthesis process of (S)-N-(2-((6-oxo-5-(trifluoromethyl)-1,6-dihydropyridazin-4-yl)amino)propoxy)-2-(1-(5-(trifluoromethyl)pyrimidin-2-yl)-1,2,3,6-tetrahydropyridin-4-yl)acetamide (structure as shown in Formula 1), and obtains a white solid. In the experimental process, it is confirmed that the compound has a good inhibitory effect on the activity of the PARP7 biological enzyme, has a good inhibitory effect on the growth of NCI-H1373 cancer cells, and has more excellent in vivo pharmacokinetic properties, and has clinical development value.

[0007]

[0008] The crystal structure of a pharmaceutical active ingredient often affects the chemical and physical stability of the drug. Different crystal forms, preparation methods and storage conditions may lead to changes in the crystal structure of the compound, and sometimes it may be accompanied by the polymorphism of other morphological crystals. Therefore, the stability of the crystal structure will have different effects on the production process, storage conditions and usage of the drug. The development of a relatively simple crystal structure is of great significance for the industrial production and application of active ingredients.

[0009] In the process of seeking a stable crystal form of the compound of formula 1, the inventors found that the compound has at least 14 crystal forms, including 7 anhydrous crystal forms and 7 solvate crystal forms, and in the process of crystal preparation, there are mutual conversion and mixed crystal phenomena among the various crystal forms, and no significantly dominant crystal form has been found. Summary of the invention

[0010] The purpose of the present invention is to provide a stable crystalline structure of "(S)-N-(2-((6-oxo-5-(trifluoromethyl)-1,6-dihydropyridazin-4-yl)amino)propoxy)-2-(1-(5-(trifluoromethyl)pyrimidin-2-yl)-1,2,3,6-tetrahydropyridin-4-yl)acetamide" (hereinafter referred to as "Compound 1") which has a single structure, high preparation repeatability, high stability, low hygroscopicity and good solubility.

[0011] The first aspect of the present invention provides a co-crystal, characterized in that it comprises a compound of formula 1 (ie, compound 1) and oxalic acid,

[0012]

[0013] Active pharmaceutical ingredient (API) molecules (compound 1) and small molecule ligand copolymer (CCF) molecules (oxalic acid) form supramolecular grids through hydrogen bonds, and after a series of stacking, assembly and arrangement, a three-dimensional crystal structure, namely a eutectic structure, is formed. The interaction and spatial binding between molecules affect the formation of network supramolecular molecules, which can improve the crystallization properties of API by affecting the crystal particle size and crystal purity. Since hydrogen bonding is essentially an electrostatic interaction with directional and saturated characteristics, it can maintain the balance and stability of the crystal. The eutectic formed by compound 1 and oxalic acid has a stable structure.

[0014] In a preferred embodiment, the molar ratio of compound 1 to oxalic acid is (2.2-1.8):1, preferably (2.1-1.9):1, more preferably (2.05-1.95):1, even more preferably (2.02-1.98):1, and most preferably 2:1.

[0015] In another preferred embodiment, the cocrystal of the present invention has a crystal structure of Form A, wherein the X-ray powder diffraction pattern of Form A has characteristic peaks at 2θ values ​​of 18.4±0.2°, 19.3±0.2°, 20.7±0.2° and 21.3±0.2°.

[0016] In a more preferred embodiment, the X-ray powder diffraction pattern of Form A further has one or more characteristic peaks at 2θ values ​​selected from the following: 13.4±0.2°, 19.9±0.2°, 22.1±0.2°, 27.5±0.2°, and 29.1±0.2°.

[0017] In a particularly preferred embodiment, the characteristic peak position shown in the X-ray powder diffraction pattern of Form A is Figure 1 , Figure 5 or Figure 8 The positions of the characteristic peaks shown in are basically the same.

[0018] The second aspect of the present invention provides a method for preparing a co-crystal, comprising mixing a compound of Formula 1 with oxalic acid in a solvent to form a suspension, stirring the suspension sufficiently, separating the suspension, and drying the suspension under vacuum to obtain crystals.

[0019]

[0020] In a preferred embodiment, in the mixing step, the molar ratio of compound 1 to oxalic acid is 1:1 to 1:10.

[0021] In another preferred embodiment, the solvent is one or more selected from ethyl acetate (EA), dichloromethane (DCM), acetonitrile (ACN), ethanol (EtOH), toluene, methyl isobutyl ketone (MIBK), methyl tert-butyl ether (MTBE), anisole, and isopropyl acetate (IPAc).

[0022] In other preferred embodiments, the drying step comprises placing the crystals in a vacuum at 40° C. to 70° C. for 2 to 24 hours.

[0023] By converting compound 1 into a co-crystal with oxalic acid, the problems of compound 1 such as multiple crystal types, poor uniformity of crystal products, and low reproducibility are effectively improved, and its production process can be simplified, making it easier to realize industrialization.

[0024] In addition, the cocrystal formed by compound 1 and oxalic acid has the characteristics of good solubility, stable crystal form, low hygroscopicity, etc., has good bioavailability, and has low requirements for storage environment.

[0025] The process of preparing the co-crystal according to the method of the present invention is simple and controllable with good reproducibility, so that the drugability of the co-crystal has good prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The X-ray powder diffraction (XRPD) pattern of the compound crystalline form A obtained in Example 1;

[0027] Figure 2 Thermogravimetric analysis (TGA) spectrum of the compound crystalline form A obtained in Example 1;

[0028] Figure 3 The differential scanning calorimetry (DSC) spectrum of the compound crystalline form A obtained in Example 1;

[0029] Figure 4 The crystal structure is determined by using the diffraction data of the compound crystalline form A obtained in Example 1 through microcrystal electron diffraction (MicroED);

[0030] Figure 5 The X-ray powder diffraction (XRPD) pattern of the compound crystalline form A obtained in Example 2;

[0031] Figure 6 This is the thermogravimetric analysis (TGA) spectrum of the compound crystalline form A obtained in Example 2;

[0032] Figure 7 The differential scanning calorimetry (DSC) spectrum of the compound crystalline form A obtained in Example 2;

[0033] Figure 8The X-ray powder diffraction (XRPD) pattern of the compound crystalline form A obtained in Example 3;

[0034] Fig. 9 It is an overlay of TGA and DSC of the compound crystalline form A obtained in Example 3;

[0035] Fig.10 This is the dynamic water adsorption (DVS) spectrum of the compound crystal form A obtained in Example 1. DETAILED DESCRIPTION

[0036] The present invention will be further described below in conjunction with specific examples. It should be understood that the following detailed description of the technical solution of the present invention with examples will help to further understand the advantages and effects of the technical solution of the present invention, and the examples do not limit the protection scope of the present invention, which is determined by the claims.

[0037] In a large number of experiments, the inventors found that compound 1 has polymorphism, and the structures of various crystal forms are unstable, and no crystal form shows obvious advantages. For example, the inventors found that there are at least 14 crystal forms of the compound, including 7 anhydrous crystal forms and 7 solvate crystal forms (summarized in Table 1 below). Since polymorphs often coexist during the synthesis process, the problem of not being able to stably repeat the preparation occurs during the repeated preparation process. Therefore, if compound 1 needs to be produced and applied, it is necessary to obtain a crystal structure with a single structure, stable performance, and good reproducibility.

[0038] Table 1 Summary of polymorphs of compound 1

[0039]

[0040] Table 1 (Continued) Summary of polymorphs of Compound 1

[0041]

[0042] Table 1 (Continued) Summary of polymorphs of Compound 1

[0043]

[0044] Table 1 (Continued) Summary of polymorphs of Compound 1

[0045]

[0046] Table 1 (Continued) Summary of polymorphs of Compound 1

[0047]

[0048] Table 1 (Continued) Summary of polymorphs of Compound 1

[0049]

[0050] Pharmaceutical cocrystals are an important form of multi-component drug crystals, which refer to the crystals formed by the drug (API) and the pharmaceutically acceptable small molecule ligand copolymer (CCF) which is solid at room temperature, combined with non-covalent bonds such as hydrogen bonds, van der Waals forces, π-π stacking, and halogen bonds at a fixed stoichiometric ratio. Cocrystals can improve the physical and chemical properties of drugs without affecting their internal structure, especially improving the solubility, dissolution rate, and bioavailability of oral solid dosage drugs, and therefore have attracted widespread attention in the industry.

[0051] In order to solve the problem of polymorphism and lack of dominant stable crystal form of Compound 1, the first aspect of the present invention provides a co-crystal, characterized by comprising a compound of Formula 1 (ie, Compound 1) and oxalic acid.

[0052]

[0053] The functional groups on the dihydropyridazine structure of the active pharmaceutical ingredient (API) molecule (compound 1) and the carboxyl groups of the copolymer (CCF) molecule (oxalic acid) form hydrogen bond structures such as O…H…O and N…H…O (e.g. Figure 4 The interaction of hydrogen bonds enables API and CCF to form a supramolecular grid together, and after a series of orderly stacking, assembly and arrangement, a three-dimensional crystal structure, namely a eutectic structure, is formed. The interaction and spatial binding between molecules affect the formation of network supramolecular molecules, which can affect the crystal particle size and crystal purity, thereby improving the crystallization properties of API. Since hydrogen bonds are essentially electrostatic interactions with directional and saturated characteristics, they can maintain the balance and stability of crystals. The eutectic formed by compound 1 and oxalic acid has a good stable structure.

[0054] In a preferred embodiment, the molar ratio of the compound to oxalic acid is substantially 2:1.

[0055] As described above, since oxalic acid contains two carboxyl groups, the "=O" and "-OH" in each carboxyl group can form hydrogen bonds with the "-NH" and "=O" functional groups on the dihydropyridazine ring of compound 1, respectively. Therefore, in theory, one oxalic acid molecule can form a stable eutectic structure with two molecules of compound 1. Although in theory, in the eutectic of the present invention, the molar ratio of compound 1 to oxalic acid is 2:1, the existence of eutectic structural units that do not meet this molar ratio is not excluded. Therefore, "substantially 2:1" means that the actual measured molar ratio of the two is (2.2-1.8):1, preferably (2.1-1.9):1, more preferably (2.05-1.95):1, even more preferably (2.02-1.98):1, and most preferably 2:1.

[0056] Considering the saturation of hydrogen bonds, the ratio between each copolymer (CCF) molecule and the active drug (API) molecule can only ensure the stability of the co-crystal structure within a certain range.

[0057] According to the present invention, the cocrystal has a crystal structure of Form A, and the X-ray powder diffraction pattern of Form A has characteristic peaks at 2θ values ​​of 18.4±0.2°, 19.3±0.2°, 20.7±0.2° and 21.3±0.2°.

[0058] In a preferred embodiment, the X-ray powder diffraction pattern of Form A also has one or more characteristic peaks at 2θ values ​​selected from the following: 13.4±0.2°, 19.9±0.2°, 22.1±0.2°, 27.5±0.2°, and 29.1±0.2°.

[0059] The X-ray powder diffraction pattern of Form A of oxalic acid cocrystal is slightly different due to the slight difference in crystal structure, which is mainly affected by the specific crystallization conditions. In some embodiments, the position of the characteristic peak shown in the X-ray powder diffraction pattern of Form A is slightly different from Figure 1 , Figure 5 or Figure 8 The positions of the characteristic peaks shown in are basically the same.

[0060] According to the second aspect of the present invention, there is provided a method for preparing a co-crystal as in the first aspect of the present invention, comprising mixing a compound of formula 1 with oxalic acid in a solvent to form a suspension, stirring the suspension sufficiently, separating the suspension, and drying the suspension under vacuum to obtain crystals.

[0061]

[0062] The API molecules and CCF molecules are coupled to each other through hydrogen bonds, without forming covalent bonds or ionic bonds, so the reaction conditions required are relatively mild. However, it is necessary to ensure that the two molecules are in full contact and reach the distance to form a hydrogen bond structure.

[0063] The suspension may be formed by any method known in the art. The present invention adopts stirring and beating method to form the suspension.

[0064] In some preferred embodiments, the beating experiment is usually carried out at room temperature to 50° C., and the beating time is usually 6 hours to 2 weeks.

[0065] In a preferred embodiment, in the mixing step, the molar ratio of the compound to oxalic acid is 1:1 to 1:10.

[0066] An appropriate excess of CCF molecules is conducive to forming a sufficient hydrogen bond structure with the API molecules. The inventors have found through a large number of experiments that even if the CCF molecules are excessive, it does not affect the structural uniformity of the formed eutectic crystals. Analysis shows that the saturation of hydrogen bonds makes the number ratio between CCF and API molecules in the crystal relatively stable.

[0067] In another preferred embodiment, the solvent is selected from one or more of ethyl acetate (EA), dichloromethane (DCM), acetonitrile (ACN), ethanol (EtOH), toluene, methyl isobutyl ketone (MIBK), methyl tert-butyl ether (MTBE), anisole, and isopropyl acetate (IPAc).

[0068] Oxalic acid is easily ionized into ionic form in highly polar solvents such as water or ethanol due to its strong acidity. In order to ensure that oxalic acid forms a eutectic with the API molecule in molecular form, it is necessary to select a solvent with poor solubility or weak polarity to fully disperse the oxalic acid molecules.

[0069] The method for separating crystals mentioned in the present invention can be any separation method known in the art, such as decantation, filtration, centrifugation, gravity sedimentation, etc. Generally, a suitable separation method is selected according to the fluidity of the suspension and the particle size of the solid particles. Commonly used methods are filtration and centrifugation.

[0070] In another preferred embodiment, the drying step comprises placing the separated crystals in a vacuum at 40°C to 70°C for 2 to 24 hours, preferably at 40°C to 60°C for 8 to 20 hours, and more preferably at about 50°C for 12 to 18 hours.

[0071] The experimental methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or conditions recommended by the manufacturers.

[0072] Unless otherwise specified, the raw materials and reagents used in the examples were purchased from commercial suppliers.

[0073] Unless otherwise specified, the reagents were used directly without purification.

[0074] Experimental instruments and conditions

[0075] X-ray powder diffractometer (XRPD)

[0076]

[0077] Thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC)

[0078]

[0079] Microcrystal Electron Diffraction (MicroED)

[0080]

[0081] H NMR spectrum ( 1 H-NMR)

[0082]

[0083] High Performance Liquid Chromatography (HPLC)

[0084]

[0085] Ion Chromatography (IC)

[0086]

[0087] Preparation of the compound of formula 1 (ie, compound 1): prepared according to the method described in Example 25 of Chinese invention patent CN115785074B.

[0088] Example

[0089] Eutectic preparation experiment

[0090] Example 1

[0091] 1 g of compound 1 and 1.1 equivalents of oxalic acid were weighed and added to a 20 mL bottle, and 10 mL of ethyl acetate (EA) was added. The resulting suspension was stirred at 50 ° C for 6 h, cooled naturally to room temperature, and then filtered to obtain a wet product, which was then placed at 50 ° C and vacuum dried for 18 h to obtain 805 mg of the product. The obtained product was subjected to XRPD, TGA, DSC, 1 H-NMR, HPLC, IC and MicroED tests.

[0092] The XRPD spectrum of the final dry product is as follows Figure 1 As shown in the TGA spectrum Figure 2 As shown in the DSC spectrum Figure 3 As shown, the crystal structure solved by MicroED is as follows Figure 4 shown.

[0093] After XRPD detection, the obtained dry product is oxalic acid cocrystal form A, which is obtained by vacuum drying the wet product at 50°C for 18 hours. The XRPD spectrum analysis data of oxalic acid cocrystal form A are shown in Table 2.

[0094] Table 2 XRPD spectrum analysis of oxalic acid cocrystal form A

[0095]

[0096]

[0097]

[0098] from Figure 2 From the TGA spectrum, we can see that the product has almost no weight loss before 105°C, and the product structure has good thermal stability. Figure 3 It can be seen from the DSC spectrum that the obtained dry product has an endothermic peak at 175.2°C. 1 H-NMR analysis proved that there was no organic reagent residue in the obtained crystal structure. After HPLC testing, the purity of the obtained dry product reached 99.3%, which corresponds to the absence of impurity peaks in the XRPD spectrum. IC detection showed that the content of oxalate ion in the obtained dry product was 7.7%, that is, the molar ratio between compound 1 and oxalate was about 2.05:1, close to the theoretical molar ratio of 2:1.

[0099] The crystal structure of the obtained dry product was determined by MicroED experiment. The crystal belongs to the monoclinic system, P2 1 (No.4) space group, unit cell parameters are α=90°,β=94.2(3)°,γ=90°,unit cell volume Z' is 2, and the asymmetric unit consists of two API molecules and one oxalic acid (C 2 H 2 O 4 ) molecular composition, the crystal structure obtained by diffraction analysis is as follows Figure 4 shown.

[0100] Example 2

[0101] Weigh 50 mg of compound 1 and 1.1 equivalents of oxalic acid into a 2 mL vial. Add 0.5 mL of EA into the vial. Stir at 50 °C for 17 h, cool to 5 °C at 0.1 °C / min and continue beating for 3 days. Centrifuge the sample, dry it at 50 °C in vacuum for 18 h, and measure the XRPD of the dry product. The XRPD spectrum is shown in the figure below. Figure 5 The XRPD pattern analysis data are shown in Table 3. The TGA and DSC test results are shown in Figure 6 and Figure 7 shown.

[0102] Table 3 XRPD spectrum analysis of oxalic acid cocrystal form A

[0103]

[0104]

[0105] XRPD results showed that the crystals obtained by the slurrying method were detected to be oxalic acid cocrystal form A.

[0106] from Figure 6 From the TGA spectrum, we can see that the product has almost no weight loss before 105°C, and the product structure has good thermal stability. Figure 7 It can be seen from the DSC spectrum that the obtained dry product has an endothermic peak at 176°C. The HPLC test showed that the product purity was 99.4%. The IC test showed that the content of oxalate ions in the obtained dry product was 7.5%, that is, the molar ratio between compound 1 and oxalate was about 2.11:1, which was close to the theoretical molar ratio of 2:1.

[0107] Example 3

[0108] Weigh 0.5 g of compound 1 and 2.0 equivalents of oxalic acid into a 20 mL bottle, add 15 mL of DCM, stir at room temperature for 12 h, filter, place the wet product at 50 ° C in a vacuum dryer for 4 h, and measure the XRPD of the obtained dry product. The XRPD spectrum is shown in Figure 8 The XRPD pattern analysis data are shown in Table 4, and the TGA and DSC test results are shown in Fig. 9 shown.

[0109] Table 4 XRPD spectrum analysis of oxalic acid cocrystal form A

[0110]

[0111]

[0112]

[0113] XRPD results showed that the crystals obtained by the slurrying method were detected to be oxalic acid cocrystal form A.

[0114] from Fig. 9 From the TGA spectrum, we can see that the product has almost no weight loss before 120℃, and the product structure has good thermal stability. Fig. 9 It can be seen from the DSC spectrum that the obtained dry product has an endothermic peak at 175.6°C. IC detection shows that the content of oxalate ions in the obtained dry product is 7.5%, that is, the molar ratio between compound 1 and oxalate is about 2.13:1, which is close to the theoretical molar ratio of 2:1.

[0115] Embodiments 4 to 10

[0116] 50 mg of compound 1 and 2.0 equivalents of oxalic acid were weighed and added to a 2 mL vial, and 0.8 mL of different solvents were added respectively. The solvents were selected as shown in Table 5. The obtained suspension was stirred at 50°C for 2 hours and then continued to be stirred at room temperature for 12 hours. The wet product was obtained after centrifugal filtration, and then the wet product was vacuum dried at 50°C for 4 hours. The obtained dry product was measured by XRPD. The results are shown in Table 5.

[0117] Table 5 Pulping results of compound 1 and oxalic acid in different solvents

[0118] Solvents Dry product XRPD Example 4 MIBK Oxalic acid cocrystal form A Example 5 MTBE Oxalic acid cocrystal form A Example 6 Anisole Oxalic acid cocrystal form A Example 7 Toluene Oxalic acid cocrystal form A Example 8 IPA Oxalic acid cocrystal form A Example 9 ACN Oxalic acid cocrystal form A Example 10 EA / EtOH (1:1, v:v) Oxalic acid cocrystal form A

[0119] From the above results, it can be seen that compound 1 and oxalic acid were slurried in different solvents, and after vacuum drying, oxalic acid cocrystal form A can be obtained. After testing, the XRPD diffraction patterns of the crystals obtained in different solvents are also basically the same.

[0120] Examples 11 to 13

[0121] 50 mg of compound 1 and different equivalents of oxalic acid were weighed and added to a 10 mL vial, and 5 mL of DCM was added respectively. The resulting suspension was stirred at room temperature for 12 h. The wet product was centrifuged and filtered, and the wet product was vacuum dried at 50 ° C for 24 h. The obtained dry product was measured by XRPD. The results are shown in Table 6.

[0122] Table 6 Pulping results of compound 1 and different equivalents of oxalic acid in DCM

[0123] Feed ratio Dry product XRPD Embodiment 11 1:3 Oxalic acid cocrystal form A Example 12 1:5 Oxalic acid cocrystal form A Embodiment 13 1:10 Oxalic acid cocrystal form A

[0124] From the above results, it can be seen that compound 1 and different proportions of oxalic acid were subjected to slurrying experiments in DCM, and after vacuum drying, oxalic acid cocrystal form A can be obtained. After testing, the XRPD diffraction patterns of the crystals obtained by reacting with different proportions of oxalic acid are also basically the same.

[0125] Performance test of oxalic acid cocrystal form A

[0126] Example 14 Rough Solubility Test

[0127] About 5 mg of oxalic acid cocrystal Form A was weighed and added to 20 μL of different solvents (the solvents are shown in Table 7) until the solid dissolved or the solvent volume exceeded 1.5 mL. The rough solubility was measured at room temperature, and the results are summarized in the following table:

[0128] Table 7 Rough solubility of oxalic acid cocrystal form A

[0129]

[0130]

[0131] From a chemical point of view, the API molecule itself does not change after forming the cocrystal structure, so it still maintains its original efficacy. As can be seen from the above table, oxalic acid cocrystal form A has good solubility in a variety of solvents, which has a very positive effect on the development of some oral drug preparations.

[0132] Example 15 Solubility determination at different pH values

[0133] Weigh 1.7 mg of oxalic acid cocrystal form A2 (containing about 20 mg of compound 1) and add them to 10 mL of pH 1.2 buffer solution, pH 4.5 buffer solution and pH 6.8 buffer solution to form suspensions. The suspensions are kept warm and stirred at 37°C. Samples are taken and centrifuged after 2 hours, 6 hours and 24 hours, and the supernatant is taken. The content of the sample in the solution is determined by high performance liquid chromatography (HPLC). The solubility results are shown in Table 8 below:

[0134] Table 8 Solubility of oxalic acid cocrystal form A

[0135]

[0136] From the results in the table, it can be seen that the solubility of oxalic acid cocrystal form A is good, which is beneficial to increase the concentration of the drug in the body and thus promote the absorption of the drug in the body. Therefore, it can be considered that the cocrystal structure of compound 1 has good drug development prospects.

[0137] Example 16 Stability Test

[0138] About 30 mg of oxalic acid cocrystal Form A was placed in an open container at 25°C / 60%RH, 40°C / 75%RH and 25°C / 92.5%RH for one week and one month, and then samples were taken for XRPD and crystal morphology testing, and chemical purity testing by HPLC. The reaction conditions and results are shown in Table 9.

[0139] Table 9 Stability evaluation of oxalic acid cocrystal form A at different temperatures and humidities

[0140]

[0141] The crystal structure characterization results show that after one month of storage, the oxalic acid cocrystal form A has no significant change in crystal form and no significant decrease in chemical purity. This indicates that compound 1 has good physical and chemical stability after forming oxalic acid cocrystal, which is beneficial to the stable preservation of the drug formed by the compound.

[0142] Example 17 Moisture absorption test

[0143] The water adsorption and desorption properties of the oxalic acid co-crystal form A obtained according to Example 1 were evaluated by DVS. 15 mg of the oxalic acid co-crystal form A was placed in a metal container, and the metal container was placed in an Intrinsic DVS instrument. At 25 °C, a cyclic humidity gradient change of 40% RH - 0% RH - 90% RH - 0% RH - 90% RH was set, and the sample went through two consecutive adsorption - desorption cycles. The difference between each step was 5% RH. At each stage, the following equilibrium criteria were used: the mass change dm / dt < 0.002% over a period of 5 min, and the minimum and maximum equilibrium times at each stage were 60 min and 360 min, respectively. The results are shown in Table 10 and Fig.10 as shown.

[0144] Table 10 Hygroscopicity experiment of oxalic acid co-crystal

[0145]

[0146] From the results of the hygroscopicity test, it can be seen that at 25 °C, for the oxalic acid co-crystal form A, when the RH < 70%, the weight gain due to moisture absorption is less than 0.2%, and there is almost no hygroscopicity. When the RH is in the range of 70% - 90%, the weight gain due to moisture absorption is less than 0.32%, and there is slight hygroscopicity. Therefore, the oxalic acid co-crystal form A has slight hygroscopicity. This indicates that when the compound exists in the form of the oxalic acid co-crystal form A, it can remain stable without strict humidity control during the production and storage of drugs. The requirements for the drug preparation process and storage conditions are reduced.

[0147] The oxalic acid co-crystal form A according to the present invention has advantages such as good homogeneity, high structural stability, good solubility, low hygroscopicity, and can be prepared repeatedly, and has good application prospects.

[0148] It should be noted that this application is not limited to the above embodiments. The above embodiments are only examples, and embodiments with the same composition and the same function and effect as the technical idea within the technical solution scope of this application are all included in the technical scope of this application. In addition, within the scope not departing from the gist of this application, various modifications that those skilled in the art can think of to the embodiments, and other ways constructed by combining some constituent elements of the embodiments are also included in the scope of this application.

Claims

1. A eutectic, characterized in that: comprising a compound of formula 1 and oxalic acid, 2. The eutectic according to claim 1, characterized in that The molar ratio of the compound to oxalic acid is (2.2-1.8):1, preferably (2.1-1.9):1, more preferably (2.05-1.95):1, even more preferably (2.02-1.98):1, and most preferably 2:

1.

3. The eutectic according to claim 1 or 2, characterized in that: The cocrystal has a crystal structure of Form A, and the X-ray powder diffraction pattern of Form A has characteristic peaks at 2θ values ​​of 18.4±0.2°, 19.3±0.2°, 20.7±0.2° and 21.3±0.2°.

4. The eutectic according to claim 3, characterized in that The X-ray powder diffraction pattern of the crystalline form A also has one or more characteristic peaks at 2θ values ​​selected from the following: 13.4±0.2°, 19.9±0.2°, 22.1±0.2°, 27.5±0.2°, and 29.1±0.2°.

5. The eutectic according to claim 1 or 2, characterized in that: The characteristic peak positions shown in the X-ray powder diffraction pattern of the crystalline form A are substantially the same as the characteristic peak positions shown in FIG. 1 , FIG. 5 or FIG. 8 .

6. A method for preparing the eutectic according to any one of claims 1 to 5, characterized in that: The compound of formula 1 and oxalic acid are mixed in a solvent to form a suspension, After sufficient stirring, the product was separated and dried under vacuum to obtain crystals.

7. The method according to claim 6, characterized in that In the mixing step, the molar ratio of the compound to oxalic acid is 1:1 to 1:

10.

8. The method according to claim 6 or 7, characterized in that: The solvent is one or more selected from ethyl acetate, dichloromethane, acetonitrile, ethanol, toluene, methyl isobutyl ketone, methyl tert-butyl ether, anisole, and isopropyl acetate.

9. The method according to claim 6 or 7, characterized in that: The drying step comprises placing the crystals in a vacuum at 40° C. to 70° C. for 2 to 24 hours.

Citation Information

Patent Citations

  • PARP7 inhibitors and uses thereof

    CN115785074B

  • Co-crystals of CDK inhibitor and MEK inhibitor and preparation method of co-crystals

    CN105753869A

  • PARP7 inhibitors and uses thereof

    CN115785074A

Cited By

  • Oxalic acid cocrystal of parp7 inhibitor and preparation method therefor

    WO2026130040A1